Recent advances in utilizing surface‐features of naturally derived nanocellulose and nanochitin for self‐cleaning and purifying applications - Lee, Donggyu; Koo, Jun Mo; Cho, Yumi; Kim, Jinsik; Kim, Soyeon; Oh, Dongyeop X.; Jeon, Hyeonyeol; Park, Jeyoung (Bulletin of the Korean Chemical Society, 2024)
Recent advancements in the utilization of naturally derived nanocellulose and nanochitin/chitosan have opened new avenues for self‐cleaning and purification applications to address environmental challenges. This review highlights the unique structural properties of bio‐based nanofibers, which are typically rich in hydroxyl groups that enhance their functionality in various industrial sectors. Through appropriate chemical modification, they can perform specific functions facilitated by carboxylic acids or amine groups. We explored the mechanisms by which these materials facilitate oil/water separation, ultrafiltration, and self‐cleaning processes, including the incorporation of inorganic nanoparticles, such as TiO2, to improve hydrophilicity and oleophobicity. Furthermore, this review discusses innovative fabrication techniques, such as spray‐assisted layer‐by‐layer assembly, which enhance the performance of nanofiber‐based coatings. We examined the potential of these materials for diverse applications, including food packaging, wastewater treatment, and personal protective equipment, emphasizing their role in promoting sustainable industrial practices. As the global emphasis on eco‐friendly solutions intensifies, continued research and development of nanocellulose and nanochitin is expected to drive significant advancements in materials science, paving the way for greener technologies. This review delves into the innovative use of naturally derived nanocellulose and nanochitin for self‐cleaning and purification applications. Highlighting their chemical modifiability and integration with inorganic nanoparticles, it explores their potential in sustainable solutions for oil/water separation, ultrafiltration, and eco‐friendly coatings, while addressing challenges in scalability.